PENGARUH FASILITAS, LOKASI DAN TARIF TERHADAP LOYALITAS MELALUI KEPUASAN PASIEN SEBAGAI VARIABEL MEDIASI PADA PASIEN POLI RUMAH SAKIT MUHAMMADIYAH SEMARANG - Anggri Vebnia; Ari Pradhanawati; Sendhang Nurseto (Universitas Diponegoro, 2013)
Quality of health care in hospitals under the spotlight of the public. So as to achieve the purpose, Rs. Roemani Semarang should consider factors - factors that can influence patient loyalty. Among them are the facilities,location, rates and satisfaction.The purpose of this study was to determine the effect of facilities, location, rates, patient satisfaction to loyalty. This research was conducted using techniques explanatory. With a sample of 100 respondents from Rs poly patient. Roemani Muhammadiyah Semarang. Data retrieved by questionnaire and the analysis paths. As a result, the variables affect facilities by 66.6% Satisfaction, Variable Location influential by 66% against the Satisfaction, Variable rates are influential to the satisfaction of 64.1%, and variable facilities, location and rates simultaneously to the satisfaction of 72.5%. Facilities variables affect the loyalty of 76.7%, an effect of variable location Loyalty 77.1% against, variable rates are influenced by 75.2% to Loyalty, Satisfaction to Loyalty Variables of 79.5% and Variables Facility, Location and Rates for loyalty through satisfaction of 88.8%. The conclusion from this study is that there is influence between facilities, location and rates for Patient SatisfactionLoyalty through. Suggestions submitted are hospitals need to improve facilities such as parking system in force, so that Rs. Roemani Muhammadiyah Semarang can maintain good things that have been assessed by the patient and the thing that is still not good.